Valuasi Ekonomi Tidak Langsung Jasa Ekosistem Mangrove sebagai Pelindung Alami Pesisir Berbasis GIS dan Metode Biaya Pengganti - Widyanti Utami A; Andi Mawaddah Zakiyah; Ade Mulawarman; Hendra Hendra (MAKILA, 2026)
This study aims to estimate the indirect economic value of mangrove ecosystem services as a natural coastal barrier using a Geographic Information System (GIS) approach and the replacement cost method. The study was conducted in Tubo Sendana District, Majene Regency, West Sulawesi Province, a coastal area with high levels of abrasion and mangrove degradation. Spatial analysis was conducted using Sentinel-2 imagery to identify the distribution, density, and length of mangrove vegetation lines (PGVM). Meanwhile, an economic analysis was conducted by comparing the protective function of mangroves with the cost of building coastal protection infrastructure in the form of concrete embankments. The results showed that the length of mangrove vegetation reached 2,960 meters with a total area of 34.29 ha and varying levels of vegetation density. The indirect economic value of mangroves as a coastal barrier is estimated at approximately IDR 16.87 billion, which represents the replacement cost if this function is replaced by artificial infrastructure. On an annual basis, this value shows significant economic efficiency compared to a hard infrastructure-based protection approach. In addition, the results of the NDVI analysis indicate a mangrove zoning pattern that can be used as a basis for ecosystem-based coastal management. This research confirms that mangroves not only serve ecological functions but also constitute natural infrastructure with high economic value. The integration of spatial approaches and economic valuation provides a strong scientific basis for supporting the formulation of sustainable coastal management policies based on ecosystems and the blue economy.